2017
DOI: 10.1161/strokeaha.116.014825
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Risks of Adverse Radiation Effects After Gamma Knife Radiosurgery for Arteriovenous Malformations

Abstract: Background and Purpose— We evaluated risk factors associated with the development of adverse radiation effects (ARE) after stereotactic radiosurgery (SRS) for cerebral arteriovenous malformations (AVMs). Methods— We evaluated 755 patients with AVM who underwent a single Gamma Knife SRS procedure with at least a 2-year minimum follow-up. Eighty-seven patients (12%) underwent previous resection and 128 (17%) had previous embolization. The median target vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 21 publications
3
51
1
Order By: Relevance
“…Although most cases of RN have been described in cases of radiation of brain metastases, RN has also been reported extensively in the neurosurgical literature for gliomas [44][45][46] and arteriovenous malformations [5,47,48]. and likely as peritumoral edema for SRS-treated meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although most cases of RN have been described in cases of radiation of brain metastases, RN has also been reported extensively in the neurosurgical literature for gliomas [44][45][46] and arteriovenous malformations [5,47,48]. and likely as peritumoral edema for SRS-treated meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,16 We previously reported that the rates of developing permanent symptomatic AREs in single-session SRS were higher in the brainstem (11%) and thalamus AVMs (7%), compared to AVMs located in other brain locations (0%-3%). 7 In their multicenter study, Cohen-Inbar et al reported that the rate of symptomatic AREs was 14.6% in patients with brainstem AVMs who under-went single-session SRS. 2 The reported rates of symptomatic AREs after VS-SRS has varied between 3% and 7%.…”
Section: Ares After Vs-srsmentioning
confidence: 99%
“…66,67 Obliteration, however, takes several years and patients are at risk for hemorrhage during the latent period. 7,66,68 With higher radiation doses or volumes treated, risks for symptomatic radiation-induced changes increases, 7,68,69 and a greater incidence is reported for AVMs in deeper anatomic locations, such as the brainstem, striatum, or thalamus. 69 With greater nidus volumes (>8-10 cm 3 ), volume-staged radiosurgery may be performed, involving multiple sessions in which roughly 8 to 10 cm 3 of the AVM nidus are treated in each session in 3-to 6-month intervals.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%
“…7,66,68 With higher radiation doses or volumes treated, risks for symptomatic radiation-induced changes increases, 7,68,69 and a greater incidence is reported for AVMs in deeper anatomic locations, such as the brainstem, striatum, or thalamus. 69 With greater nidus volumes (>8-10 cm 3 ), volume-staged radiosurgery may be performed, involving multiple sessions in which roughly 8 to 10 cm 3 of the AVM nidus are treated in each session in 3-to 6-month intervals. [70][71][72] Annual MRIs and catheter angiography at 36 months after treatment are usually obtained to monitor treatment response.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%